Biomineralisation to improve properties of polymer modified concrete for chloride environments. (23rd May 2023) - Mohammed, Hazha; Giuntini, Francesca; Simm, Alan; Sadique, Monower; Shaw, Andy; Nakouti, Ismini; Bras, Ana
Highlights: Recyclable polymers can enhance the durability characteristics of concrete to a certain limit. Recyclable polymers were used to immobilise and protect the bacteria. Bacteria can precipitate CaCO3 before and after being immobilised to recyclable polymers. The bacteria play a significant role in controlling chloride and water migration in the concrete. Abstract: This research compares the performance of three types of polymer-modified concrete (TPE, LDPE/EVA, and PCL) if bacteria-based solutions are used for reinforced concrete (RC) structures designed for a compressive strength higher than 50 MPa in chloride environments. The aim is to understand the impact on mechanical and durability performance of concrete. These recyclable polymers' use is crucial to increasing the strength at 28 and 60 days. At 60 days, all polymer-modified concrete reached a compressive strength higher than 60 MPa. The use of bioproducts is crucial to lowering the open porosity values to 4%. However, the use of bioproducts tends to delay the increase of concrete's compressive strength with time, especially until the 14 days. The existence of tetrahedron and pyramid structures in polymer-modified bio concrete indicates that calcite is present, and the quantity of calcium carbonate in the polymer-modified bio concrete is significantly higher than in plain bio-concrete or even plain. The bioproduct plays a dominant role in the capillary control and prevents water migration more effectively in comparison to the use of different polymers in concrete. The bioproduct substantially minimise the migration of chlorides to 7 × 10 −12 m 2 /s, a water-soluble ion in wet/humid concrete porous medium environments, but also at low relative humidity environments, as it happens when the concrete is exposed to capillary suction. The highest electrical resistivity values have been recorded in TPE bio-concrete.